Effect of Multidirectional Forging and SIMA Process on Mechanical and Tribological Behavior of Hypereutectic Al-18 Wt.% Si Alloy - Choudhary I.N.; Sinha N.K.; Mahali M.; Singh J.K. (My University, 2025)
In the present work microstructure, mechanical and tribological characteristics of Al-18 wt.% Si alloy produced using the traditional gravity casting, multidirectional forged (MDF) at 300 °C, and strain-induced melt activation (SIMA) processed samples have been studied and compared. Physical and chemical characterization of all sample have been done through X-ray diffraction, optical microscopy, scanning electron microscopy (SEM) and atomic force microscopy (AFM), mechanical and tribological properties such as tensile strength, % elongation, hardness, density, porosity, wear rate, and coefficient of friction were investigated. It was observed that SIMA processed sample having a microstructure made up of globular α-Al grains and primary Si particles in place of dendrite and acicular phase. Optimized SIMA processed sample (HT 2) having 10% higher hardness value than cast and 5% higher than MDF samples, similarly tensile strength and % elongation having 40% and 8% higher value as compare to cast and 30% and 4% higher than the MDF sample due to refinement of primary Si, eutectic phase and spherical morphology. Fractograph observation indicate that fracture mode shifted from brittle to ductile mode. Wear rate increases and coefficient of friction (COF) decreases as we increase the static normal load (SNL) and sliding velocity (SV), in case of all samples but SIMA processed sample having lower wear rate and COF as compare to cast and MDF. © 2023, The Author(s), under exclusive licence to Springer Nature B.V.